HUBUNGAN ANTARA POLA HIDUP SEHAT DAN KEBUGARAN JASMANI SISWA SMA NEGERI 2 KABANJAHE - Sitepu, Deasyi Natalia; Sinuraya, Janwar Frihasan; Martauli, Elvin Desi (JURNAL CURERE, 2023)
A healthy lifestyle is the basis for developing good physical fitness, so that you can complete routine tasks without feeling tired and participate in various extracurricular activities. Because lifestyle has a big influence on life and health, especially now that many new diseases are emerging, it is very important to maintain a healthy lifestyle in order to have a fit body. The aim of this research is to analyze the relationship between healthy lifestyle and physical fitness of students at SMA Negeri 2 Kabanjahe. This research method uses a quantitative approach and correlation is used for this type of research. The population of this study consisted of students from SMA Negeri 2 Kabanjahe. The sample for this research was X, XI, totaling 55 using the census. This research's data collection technique uses a questionnaire to measure healthy lifestyle patterns to identify students' lifestyle habits. Meanwhile, the MFT test measures physical fitness. SPSS version 20 was used to analyze the data in this study which included descriptive statistics, Kolmogorov-Smirnov normality test, and Spearman rho correlation test. SPSS 20.0 was used to analyze the data in this study which included descriptive statistics, Kolmogorov-Smirnov normality test, and Spearman rho correlation test. The research results showed that the average score for a healthy lifestyle was 90.11% with the highest result being 117 and the lowest result being 56. The average fitness score was 48.5 (maximum) and 20.4 (minimum). The correlation test shows the value of healthy living and physical fitness of students (r=0.051, p=0.632 > 0.05). So it can be concluded that there is no significant relationship between a healthy lifestyle and the physical fitness of SMA 2 Kabanjahe students.